2006
DOI: 10.1080/02757540600687962
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variations of phytoplankton in the Gulf of Venice (Northern Adriatic Sea)

Abstract: Spatial and temporal variations of phytoplankton community structure were studied in the Gulf of Venice (Northern Adriatic Sea) from February 1999 to December 2001 (INTERREG II, Italia-Slovenia project). Phytoplankton samples were collected, with a monthly frequency, at 11 stations in the basin. Abundance, biomass, and species composition were considered. Synthetic descriptors were used in order to evaluate the main succession pattern and to cluster communities that typify different hydrological conditions. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 40 publications
2
57
1
1
Order By: Relevance
“…Besides, the slightly higher values of chlorophyll-a in the deepest layer at both stations are a clear indicator of photosynthetic activity of the bottom SL and thus water transparency. This leads us to consider the areas as trophically much similar than previously reported in literature (e.g., Alberighi et al, 1997;Pugnetti et al, 2003Pugnetti et al, , 2004Bernardi Aubry et al, 2006).…”
Section: Trophic Variability Of the Nw Adriaticmentioning
confidence: 77%
See 1 more Smart Citation
“…Besides, the slightly higher values of chlorophyll-a in the deepest layer at both stations are a clear indicator of photosynthetic activity of the bottom SL and thus water transparency. This leads us to consider the areas as trophically much similar than previously reported in literature (e.g., Alberighi et al, 1997;Pugnetti et al, 2003Pugnetti et al, , 2004Bernardi Aubry et al, 2006).…”
Section: Trophic Variability Of the Nw Adriaticmentioning
confidence: 77%
“…1). Many authors (e.g., Alberighi et al, 1997;Pugnetti et al, 2003Pugnetti et al, , 2004Bernardi Aubry et al, 2006) have classified E06 as a station that is influenced by the Po river run-off and characterized by meso-eutrophic waters, while they have represented C10 as a meso-oligotrophic station that is only partially influenced by the Po river discharge; the latter occurs particularly during intense stratification periods, when the Po plume eventually turns north-eastwards. In particular, whereas Alberighi et al (1997) referred to the two stations as trophically different, Pugnetti et al (2003) could not typify a significant difference in community composition, because a prevalence of tolerant species is observed in the whole area of the North Adriatic Sea.…”
Section: The Area Ismentioning
confidence: 99%
“…In this study Skeletonema marinoi, was observed sporadically in the late winter period, and was related to nutrient rich waters. This species is a characteristic winter diatom of the north-western Adriatic (Bernardi Aubry et al, 2006;, and we found it thriving in waters under Po River influence (supplementary Fig 3).…”
Section: Seasonal Succession Of the Phytoplankton Speciesmentioning
confidence: 89%
“…Bernardi Aubry et al (2006) found that main phytoplankton seasonal pattern in the northern Adriatic did not change significantly among years. The seasonal absence of many species is explained by periodicity and rarity, and even though we do not record specimens, some might be present.…”
Section: Seasonal Succession Of the Phytoplankton Speciesmentioning
confidence: 99%
See 1 more Smart Citation